Institutional quality, insurance penetration and Economic growth in sub-saharan Africa - OBENG NANA AKUA DORCAS (knust, 2025)
A thesis submitted to the Department of Accounting and Finance in fulfillment of the requirement for the award of Doctor of Philosophy (PhD) Business and Management